Masterpieces on Japan by Foreign Authors From Goncharov to Pinguet - Saeki, Shōichi; Haga, Tōru (Springer Nature, 2023)
This open access book includes forty-one chapters about foreign observers' discourses on Japan. These include a wide range of perspectives from the travelogues of curious visitors to academic theses by scholars, which offer us a broad spectrum of contents, reflecting a variety of attitudes toward Japan. The works were written during the period from the 1850s to the 1980s, a timespan during which Japan became, in stages, more open to the outside world after a long isolation under the Tokugawa shogunate. From the perspective of "Japanology," one can discern three distinct periods of rising interest in the country from abroad. The first tide of such interest came shortly after the opening of Japan, when various foreign travelers, including those who could not be included in this book, came over and wrote down their impressions of the country-which was, for them, a land of mystery and mystique, which had just opened its doors to them. The second wave arose at the beginning of the twentieth century, just after the Russo-Japanese War, when Japan again generated a remarkable surge of interest as a "miracle" in Asia that had pulled off the wondrous feat of defeating a white superpower. The third wave was more recent, which took place from the late 1960s to the 1980s, a period of high economic growth when the "miracle" of Japan's remarkable economic recovery from the defeat of World War II attracted enthusiastic and curious attention from the outside world once again. It is not the intention of this book to directly highlight such historical transitions, but these forty-two brilliant mirrors (forty-one chapters, including forty-two discourses), even when looked in casually, provide us with unexpected insights and various perspectives. Shōichi Saeki (1922-2016) was Professor Emeritus, the University of Tokyo. Tōru Haga (1931-2020) was Professor Emeritus, International Research Center for Japanese Studies.